Impact of a Residency-Run Emergency Medicine Podcast Summary on Learning Retention and Engagement - Christopher Reilly; Bobbie Ann Adair White; Katherine Pattee; Hannah Blakely; Reuben Strayer; Sergey Motov; Antonios Likourezos; Rukhsana Hossain; Sarah Kabariti; Jefferson Drapkin (Western Journal of Emergency Medicine, 2026)
Introduction: Podcasts have become a widely used educational tool in emergency medicine. In this study, a podcast was used as the intervention. This podcast consisted of a brief audio summary of weekly in-person conference content produced by residents and faculty. We assessed whether a resident-led, curriculum-based podcast summary improved knowledge retention and learner engagement compared to a standard written summary format. Methods: This mixed-methods prospective cohort study conducted at a single urban academic hospital included 54 emergency medicine residents and approximately 66 attending physicians. The study unfolded in three phases: eight weeks of standard written conference summaries (control); followed by eight weeks of written plus podcast conference summaries (intervention); and a four-week post-intervention period with surveys. The primary outcome was knowledge retention, measured by weekly postconference quiz scores comparing the written-summary phase (control) with the podcast phase. Secondary outcomes included learner satisfaction, podcast usage patterns (downloads and self-reported listening), and self-reported impact on clinical application of conference content. Data included quiz scores, survey responses, and podcast analytics. Statistical comparisons of quiz performance were made using paired t-tests. Thematic analysis of open-ended responses was performed using Braun and Clarke’s framework. Results: Mean quiz scores were 73.1% (standard deviation [SD] 6.6) during the written phase and 73.7% (SD 14.4) during the podcast phase with no statistically significant difference in weekly quiz performance between conditions (paired t-test, P = .92). An exploratory linear trend analysis suggested a steeper week-to-week improvement during the podcast phase, but this post-hoc finding should be interpreted cautiously. Although the podcast did not improve knowledge retention compared with the existing written summary, learners reported high satisfaction, perceived reinforcement of key concepts, and convenient asynchronous access. Conclusion: In this mixed-methods study, a residency-run podcast summary did not improve quiz-based knowledge retention compared with an existing written conference summary. However, learners reported high satisfaction, perceived reinforcement of key concepts, and convenient asynchronous access.